OH LORD, WON'T YOU BUY ME A MERCEDES BENZ OR, THERE IS A THERE THERE - Okerson, Ann (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1994)
An overview of the current situation of scholarly research and publication on the Internet, with suggestions for further developments.